The Role of Functional Neuroimaging in Mild Cognitive Impairment - Marcos, Alberto; Barabash, Ana; Gil, Pedro; Encinas, Marta; de Juan, Ramon; Payno, Maria; Ancin, Ines; Vazquez, Blanca; Cabranes, Jose A. (Current Medical Imaging, 2006)
Mild Cognitive impairment (MCI) is a frequent problem in the elderly, since many of MCI subjects progress into Alzheimer's disease (AD). Recently new treatment options have been developed that may alter or delay the rate of AD deterioration. Wherefore, detecting and recognising patients that have a higher risk of developing dementia allows for the planning of correct treatments, future care and research purposes. Although there are no markers that certainly predict the progression to dementia, some useful clinical or biological features have been reported. A reduced perfusion, glucose metabolism or atrophy in local areas of the cerebral cortex assessed by functional or conventional imaging technics, some genes, CSF proteins and psychological test, have been described as risk factors for the development of AD. Even if there is not one single diagnostic method with enough sensibility or specificity to allow a sure outcome, combining early clinical, regional cerebral blood flow and genetics markers we can improve accuracy on predicting the progression from MCI to AD. We review the clinical diagnostic criteria of MCI, the increasing literature about its diagnosis, and we describe the recent findings under the light of our experience following up patients during 5 years.
Keywords: Alzheimer' s disease